Direct Lungs Targeting: An Alternative Treatment Approach for Pulmonary Tuberculosis - Vidyadevi, Bhoyar (Asian Journal of Pharmaceutics (AJP), 2022)
In the present review, authors are tried to analyze existing and advanced formulation with novel drug delivery and potential treatment approach with an aim to determine current knowledge gaps to control pulmonary tuberculosis (TB). Currently, in the market single as well as in fixed-dose combination tablet dosage forms are available. However, the conventional route of administrations, the oral route has drawbacks. Direct targeting of drug to the lungs is not achievable. Due to high dose of anti-TB drugs and shorter half life, the dosing frequency is more, resulting into hepato-toxicity and other side effects associated with them. One more challenge in TB treatment is lengthy treatment protocol. So there is a need of the novel treatment approach than the conventional, which is able to target the site of infection, where Mycobacterium resides. For pulmonary infections where direct drug administration to the lungs is desirable, the inhalation mode of drug delivery is the most advantageous. By taking advantages of the pulmonary route as well as the novel drug delivery system, we might be able to resolve the above challenges. Direct lungs targeting with inhalable microparticulate and nanoparticulate systems could potentially reduce dose, dosing frequency and to target the pulmonary site. Novel drug delivery systems such as Niosomes, Liposomes, Dendrimers, Microencapsulated particles, Microspheres, and Hydrogels have been identified as new antitubercular drug delivery strategies. These drug delivery systems may emerged as a promising solution to overcoming the limitations of traditional formulations and treating drug resistance, indicating that new advances in this field are possible.